Using cardiovascular imaging modalities to determine cardiac disorders before starting sports activities - Özgür Ceylan; Timur Meşe; Alper Hazım Gürsu (KARE Publishing, 2017)
Objective: We re-examined children who had previously been declared eligible to participate in competitive sports activities for cardiac disorders, using cardiac investigation protocol. Methods: Total of 250 children (224 males [89.6%], and 26 females [10.4%]) between the ages of 8 and 17 years who had just started or were already engaged in sports activities were included in the study. Participants had detailed physical examination evaluated by a pediatric cardiologist. Those with findings suggesting cardiac disorder in their history and/or physical examinations, and/or 12-channel electrocardiography (ECG) were examined with echocardiography (ECHO), 24-hour Holter monitoring, and exercise test. Results: Mean duration of participation in sports activities was 13 months. Among all, 10.4% of the children had abnormalities on ECG. ECHO demonstrated cardiomyopathy in 1, mitral valve prolapse in 2, tricuspid insufficiency in 2, and mitral insufficiency in 1 participant. Holter monitoring revealed non-sustained ventricular tachycardia attacks in 1, and supraventricular tachycardia in another child. Three were ultimately disqualified from partaking in competitive sports. Conclusion: Sports and medical communities must work together to establish study protocols to prevent sudden death related to sports and to make these activities safer for athletes. Pediatric cardiology consultation for young athletes before they start sports activities is needed.